The bishop's pawn [large type] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2018)
History notes that the ugly feud between J. Edgar Hoover and Martin Luther King, Jr., marked by years of illegal surveillance and the accumulation of secret files, ended on April 4, 1968 when King was assassinated by James Earl Ray. But that may not have been the case. Now, fifty years later, former Justice Department agent, Cotton Malone, must reckon with the truth of what really happened that fateful day in Memphis. It all turns on an incident from eighteen years ago, when Malone, as a young Navy lawyer, is trying hard not to live up to his burgeoning reputation as a maverick. When Stephanie Nelle, a high-level Justice Department lawyer, enlists him to help with an investigation, he jumps at the opportunity. But he soon discovers that two opposing forces--the Justice Department and the FBI--are at war over a rare coin and a cadre of secret files containing explosive revelations about the King assassination, information that could ruin innocent lives and threaten the legacy of the civil rights movement's greatest martyr. Malone's decision to see it through to the end ---- from the raucous bars of Mexico, to the clear waters of the Dry Tortugas, and ultimately into the halls of power within Washington D.C. itself ---- not only changes his own life, but the course of history.